The Impact of Short-Term Employment for Low-Income Youth: Experimental Evidence from the Philippines - Emily A. Beam; Stella Quimbo (Institute of Labor Economics (IZA), 2021)
We use a randomized field experiment to test the causal impact of short-term work experience on employment and school enrollment among disadvantaged, in-school youth in the Philippines. This experience leads to a 4.4 percentage point (79-percent) increase in employment 8 to 12 months later. While we find no aggregate increase in enrollment, we also do not find that the employment gains push youth out of school. Our results are most consistent with work experience serving as a signal of unobservable applicant quality, and these findings highlight the role of temporary work as a stepping- stone to employment for low-income youth.
Keywords: J24; J08; O15; 330; short-term employment; work experience; ALMP; experiment